Penerapan Metode Dempster Shafer Pada Aplikasi Gangguan Kecemasan Sosial Berbasis Android - Putri, Dini Ridha Dwiki; Fahlevi, Muhammad Reza; Nisa, Hairun (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Social anxiety disorder is a mental health disorder characterized by a fear of being watched, judged, or embarrassed by others. Anyone can actually experience fear or anxiety when interacting with other people. But for sufferers, this fear is experienced excessively and gradually over time. As a result, this condition affects interaction with other people, productivity at work, or achievement at school. For this reason, we need a system that can carry out psychological tests for social anxiety disorder, which are dominated by sufferers with an age range of 10-17 years and even more, sufferers who have anxiety and are afraid to tell what they are experiencing can use this application before deciding to consult a psychologist. . The application of the Dempster Shafer Method in this application provides accurate results on the percentage level of confidence in social anxiety disorder by transferring expert (psychological) knowledge into an Android-based application, the system will be said to be successful if it shows the same or close percentage. Implemented into Android-based software and the application is dynamically displayed and user friendly.